Anti-phospholipase A2 receptor antibody in idiopathic membranous nephropathy: A report from Iranian population - MohammadReza Ardalan; Ali Ghafari; Fatemeh Hamzavi; Hamid Nasri; Behrooz Baradaran; Jafar Majidi; Behrooz Nikbin (Society of Diabetic Nephropathy Prevention, 2013)
Background: Idiopathic Membranous Nephropathy (iMN) is the most common cause of nephrotic syndrome in adults. Approximately one third of patients with iMN progress to end-stage renal disease. Anti-phospholipase A2-receptor (anti-PLA2R) antibodies are present in patients with iMN and appear to play a role in the pathogenesis of iMN. Objectives: In this study, we explored the prevalence of anti-PLA2R antibodies in a cohort of patients with iMN in Iran. We also sought to determine circulating levels of anti-secretory PLA2 (anti-sPLA2) antibodies in those with anti-PLA2R antibodies. Patients and Methods: Using an indirect immunofluorescence assay, we measured anti-PLA2R antibodies in a group of patients with iMN in Iran. The serum levels of anti-sPLA2 antibodies were also measured in those with positive results for anti-PLA2R antibodies. Results: We studied 23 patients with iMN (M/F 12/11, 34±9.8 year), two patients with secondary MN and five patients with the nephrotic syndrome of other causes.Anti-PLA2R antibodies were detected in 17/23 (74%) of patients with iMN, but not in those with secondary MN or other forms of primary glomerular diseases. We found no correlation between anti-PLA2R antibody titer and the degree of proteinuria. We found high titers of anti-sPLA2 antibodies in a subset of patients with high levels of anti-PLA2R antibodies. Conclusions: Anti-PLA2R antibodies are specific for iMN. Proteinuria may also reflect glomerular structural damage rather than immunological activity of the disease. The preliminary idea of any presumptive role of anti-sPLA2antibodies in iMN needs further investigation.